6 PENINGKATAN KECERDASAN LINGUISTIK MELALUI MENDONGENG CERITA RAKYAT (Penelitian Tindakan di TK B PAUD Dahlia, Lampung Selatan Tahun 2016) - Kurniasih, Siti (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2016)
ABSTRACT The aims of this research were to describe the process of the increasing students’ linguistic intelligence and to knows how far the result of the increasing by students’ linguistic intelligence through story the legend. Respondent of the research involved of 15 children from grade B at PAUD Dahlia kindergarten. The method of this research was used by Kemmis and Taggart models and it does by 8 times of meeting by two cycles. The data analyzed by using quantitative and qualitative approach. The result of this research were an increasing by the students’ linguistic intelligence through story the legend, it was evidence by the quantitative and qualitative data. At the quantitative data it showed of pre-cycle 53,25%, it was increase to cycle I 19,42% be 72,67%, and it was increase to cycle II 16,64% be 89,31%, then at the qualitative data shows the increasing of linguistic intelligence by process that the teacher tells the story by using many kinds of media, the children give attention and respond it, and then the children tell the story based on their imagination. Key words: linguistic intelligence, story the legend, early childhood, action research